Unveiling the uncommon: invasive adenocarcinoma cervix presenting during pregnancy: a rare case report - Tauro, Sheral R.; Singh, Yanglem A.; Namoijam, Basanti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Adenocarcinoma of the cervix presenting during pregnancy is an exceedingly rare occurrence, and the optimal management approach remains uncertain due to limited reported cases. Here we are presenting a case of a multiparous lady who presented with complaints of amenorrhoea for 3 months, pain abdomen, spotting per vaginum, mass felt per vaginum. Ultrasonography showed single live intrauterine pregnancy at 11 weeks 4 days of gestational age with an ill-defined hyperechoic lesion measuring 4.36×4.92×4.16 cm in cervix. HPE of cervical biopsy confirmed cervical adenocarcinoma-endocervical type, grade 2. On MRI, a heterogeneous exophytic irregular mass involving the external os, protruding into the upper vaginal cavity was identified with infiltration into the anterior upper vaginal wall, pelvic lymphadenopathy, and sub-centimetric inguinal lymph nodes were observed. The patient underwent radical hysterectomy with bilateral pelvic lymph node dissection. The surgical specimen exhibited stromal invasion exceeding 5mm in depth and width greater than 7mm, involving entire cervical wall with lympho-vascular space invasion. The tumor was ER/PR negative, strongly positive for P16, and HPV studies were also positive. Adjuvant external beam radiotherapy (EBRT) was administered to the pelvis, and the patient is currently in remission.